Calcium chloride-based systems for metal electrodeposition. (10th January 2022) - Hartley, Jennifer M.; Allen, Jack; Meierl, Julia; Schmidt, Alexei; Krossing, Ingo; Abbott, Andrew P.
Abstract: Novel eutectic mixtures have been produced using calcium chloride hexahydrate as the hydrogen bond acceptor, together with ethylene glycol as the hydrogen bond donor. The liquids are found to have increased conductivity, decreased viscosity and a lower glass transition temperature compared to most deep eutectic solvents produced using quaternary ammonium salts. Additionally, metal speciation was found to be almost the same as in a commonly-used choline chloride: ethylene glycol DES, despite the difference in water content. Calcium chloride is an interesting component as it is a waste product from the Solvay process hence it is inexpensive, and also has low toxicity. The electrochemical properties of four different metals in these eutectic mixtures were investigated, and critically, it was shown that metallic iron, cobalt and nickel could be electrodeposited at ambient temperatures without the need for additives.